Pengaruh Aplikasi Tik Tok Terhadap Prilaku Anak Usia 5 Sampai 10 Tahun di Desa Sumber Agung Kec. Sungkai Utara - Endang Purnama; Nita Zakiah; Muhammad Zaenal Arifin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Along with technological advances,many social media can be accessed by children until they are old. Especially during the panademic,children studied at home and used accessories in learning to use gadgets, so that here children want to easily access anything via gadgets, one of which is the tiktok application. lately, elementary school-age children have been imitating various content found in the tiktok application. This content creates a problem if the content that is viewed or imitated does not reflect something good, this will here an impact on the child's character. In this research using qualitative methods of problem research. The result of this research is that many children experience changes or declines in moral ethics which are currently more or less influenced by the use of gadgers.the things that influence it are the conten that children see through the tiktok aplication. Not only that, the lack of parental supervision in using gadgets.